(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
Through the analysis of three contributions by Stefano Rodotà to Church-State law (“Seeking freedom”, “The life and the rules. Between law and non-law” and “Why secular”) the author aims at reconstructing the evolution of the thought of Rodotà along his career. The books represent a gradual widening of the secularism of Rodotà. While ’Seeking freedom’ concentrates on the necessity to affirm secularism by reducing the privileges granted to the Italian Catholic church, ’The life and the Rules’ affirms the importance of the law in granting to the individual the basic dignity in the most intimate and personal choices. Finally, in ’Why secular’, Rodotà comes to the conclusion that secularism is the essence not only of a just government, but of a true law.